Analisis Faktor Risiko Cost of Quality Terhadap Failure Cost Pada Pelaksanaan Pekerjaan Struktur Gedung Bertingkat - Viorenza Everlyn; Arief Setiawan Budi Nugroho; Andreas Triwiyono (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2023)
The success of the construction sector is inseparable from cost and quality, it is reported that identified quality failures reach 5-20% of the project contract value. To reduce quality failures and failure costs in the implementation of construction projects, it is necessary to provide cost of quality (COQ) assistance. In this research, reinforced concrete construction was chosen as the object of COQ assistance because it is a critical part of the structure. The purpose of this research is to categorize the COQ from internal and external factors and analyze the potential costs incurred for these failure factors. Analysis of the cost of quality failure was carried out based on the weighting of the results of the pairwise comparison matrix to obtain consistency index (CI) and Consistency ratio (CR) values and using the Kruskal Wallis test as a non-parametric test approach. The results of this research indicate that COQ greatly influences profitability, where the failure of the highest internal quality is the work method factor which affects the failure of the final concrete result in the form of structural and visual defects, while the highest external quality failure is the product selection factor at the client's request which causes the resulting construction products are not in accordance with the specifications or not in accordance with the expected function. Based on the causal factors of the quality failure, the implementation control process affects the result of product quality to the point of causing clients to demand, replace, and repair during the warranty period. Failure costs that affect the highest contract value amounted to 7.26% of internal failures and 6.40% of external failures.